The Death Penalty: History, Exonerations, and Moratoria - Martin Donohoe (Social Medicine Publication Group, 2019)
Today's topic is the death penalty. I will discuss multiple areas related to the death penalty, including its history; major Supreme Court decisions; contemporary status; racial differences; errors and exonerations; public opinion; moratoria; and ethics and morality. I will also refute common myths, including those that posit that the death penalty is humane; equally applied across the states; used largely by "Western" countries; color-blind; infallible; a deterrent to crime; and moral.